2016
DOI: 10.1097/nmd.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Beliefs and Attitudes Toward Mental Illness Across Five Nations

Abstract: Negative attitudes toward people with mental illness are a widespread concern and may vary across countries. This study used a 36-item questionnaire to compare attitudes toward people with mental illness and beliefs about the causes of mental illness among medical students from the United States, Brazil, Ghana, Nigeria, and China (N = 1131). Exploratory factor analysis identified the underlying factor structure of the questionnaire, and analysis of covariance was then used to compare factors representing four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…The question remains as to what can be done to reduce stigma both among medical students and in Chinese society more broadly. As noted above, the results from China reported here are consistent with a previous cross‐national survey involving 5 different countries (Stefanovics et al, ). In that study, medical students from the United States exhibited significantly more positive and progressive attitudes than those from other countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question remains as to what can be done to reduce stigma both among medical students and in Chinese society more broadly. As noted above, the results from China reported here are consistent with a previous cross‐national survey involving 5 different countries (Stefanovics et al, ). In that study, medical students from the United States exhibited significantly more positive and progressive attitudes than those from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma damages social interaction through lack of knowledge (ignorance), negative attitudes towards a group (prejudice), and functional exclusion (discrimination) (Ighodaro, Stefanovics, Makanjuola, & Rosenheck, ). Stigma can also significantly impede treatment initiation, continuation, and outcome, and reduces access to employment, housing, and social relationships (Stefanovics et al, ). To address stigma, there is a need to better understand its origins (Lauber & Rössler, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative and stigmatising public attitudes towards people who are mentally ill can impact the prevention and treatment interventions, together with the overall quality of life (Barke et al, 2011). Moreover, previous studies in Nigeria, Ghana, and Kenya (Iheanacho et al, 2014;Makanjuola et al, 2016;Stefanovics et al, 2016) have shown that individuals who hold a religiomagical explanatory model of causation show more stigmatization towards people with mental illness. In Nigeria, Cohen et al (2016) reported that people who are influenced by traditional beliefs in supernatural causes and remedies, may lead to an unhelpful or health-damaging response to mental disease, and a delay in seeking appropriate care.…”
Section: Proposals For Improvementmentioning
confidence: 99%
“…Belief in supernatural or spiritual causes of mental illness is common in Ghana, and consequently people seek care from traditional healers or evangelical pastors. [8][9][10][11] Recent legislation (Mental Health Act 846, 2012) seeks to expand access to psychiatric care, protect patients' rights and augment community-based services. The Act created a mental health authority for whom one initial priority is the improvement of care in prayer camps, although this aspect of the law has yet to be implemented.…”
mentioning
confidence: 99%